Innovations in Law Education: Combining Traditional and Innovative Technologies in Legal Education - Teshaboeva Shahodat (International Journal on Integrated Education, 2022)
The article deals with traditional and innovative technologies in legal education. The author analyzes new technologies that are gaining popularity among teachers in connection with the adoption of the state education standard. Both positive and negative aspects of the studied technologies are indicated.